Comment on "Climate and agricultural land use change impacts on streamflow in the upper midwestern United States" by Satish C. Gupta et al. Issue 9 (24th September 2016) - Foufoula‐Georgiou, Efi; Belmont, Patrick; Wilcock, Peter; Gran, Karen; Finlay, Jacques C.; Kumar, Praveen; Czuba, Jonathan A.; Schwenk, Jon; Takbiri, Zeinab
Abstract: This comment cautions against dismissing agricultural practices as a significant cause of hydrologic change in Midwestern agricultural landscapes. Key Points: Subsurface tile drainage alters water cycle dynamics Quantifying the nature of subannual hydrologic change and its cascade to sediment and nutrient transport is essential for management